THE DEVELOPING EUROPEAN CRIMINAL POLICY - Udvarhelyi, Bence (European Integration Studies, 2017)
One of the main principles of the functioning of the European Union is the principle of conferral, according to which the Union shall act only within the limits of the competences conferred upon it by the Member States in the Treaties. The Founding Treaties of the European Communities originally did not contain any express provision in connection with criminal law; therefore it was a common opinion for a long time that the European Communities did not have legal competence in criminal matters. However, it cannot be said that Community/EU law and national criminal law were entirely independent of each other. Due to several factors, criminal law is increasingly becoming the focus of European legislation and European legal instruments already exert influence on the existing national legal frameworks of substantive criminal law and criminal procedure law. With the reformed and renewed framework of the Treaty of Lisbon, this tendency will be even stronger in future. Although it can be stated that national law is heavily influenced by EU law, the Union still failed to acknowledge criminal policy as an autonomous European policy. However, after the adoption of the Treaty of Lisbon, European criminal policy slowly began to develop.